Emotional storytelling: Sensational media and the creation of the HIV sexual predator - Kilty, Jennifer M and Bogosavljevic, Katarina (Crime, Media, Culture: An International Journal, 2019)
More than 180 people in Canada have faced criminal charges related to HIV nondisclosure. Media coverage is often sensational and commonly portrays people living with HIV as hypersexualized threats to the (inter)national body politic. This article analyzes mainstream news media coverage of four HIV nondisclosure cases to examine how the accused (two men, two women) are constructed as sexual predators, which we found occurs through two key discursive moves. First, by tying the narrative to stereotypical conceptualizations of hegemonic and toxic masculinity and pariah femininity to construct the individual as promiscuous, hypersexual and dangerous. Second, by crafting a narrative that evokes complex moral emotions; notably, these include the ‘negative’ emotions of anger, disgust and fear. Given that racialized men are disproportionately represented and demonized in media accounts, and the tense race relations in the current western political landscape, it is important to consider how emotions (rather than medical evidence of the risks of transmission, intent to infect or actual transmission) might contribute to shaping punitive mentalities and the harsh application of the law. By examining how race, gender, class and sexuality are mobilized to construct narratives of Black masculinity as inherently toxic and women’s sexual freedom as exemplifying pariah femininity, and the ways in which the coverage evokes negative moral emotions, we contend that media coverage shores up moralized discourses about sexuality, masculinity and femininity and HIV/AIDS.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQxNjU5MDE4NzczODEz